Proposta de um núcleo de ambientes itinerantes de aprendizagem no desenvolvimento socio-criativo-educacional para alunos da educação inclusiva - Araújo, José Carlos da Cruz (Universidade do Vale do Rio dos Sinos, 2021)
This article aims to verify the possibilities of the actions of the Center for Itinerant Learning Environments, which will enable the development of a pedagogical practice aimed at meeting the educational needs of students inserted in Inclusive Education, for this we will develop works with the sectors of pedagogy, psychology, and physical education, translating into a practical format, all theoretical activities, from the various disciplines that make up the school curriculum. In this exploratory research of qualitative approach, we present a study with articles focused on the development of activities with inclusion students. work that will be developed by this Nucleus is based on The Ignatian Pedagogy and comes to contribute to the understanding of actions and didactic functions in pedagogical activities and contents developed in the classroom, consequently the human and integral formation of students, attended by inclusive education. With the purpose of working the cognitive, affective, and motor repertoires, from psychomotor works with an end, to develop the inborn reflexes, adding in their experience practical experiences of knowledge construction, providing, in addition, pleasure, through playful activities, promoting the growth of an autonomous, critical, spontaneous, questioning, organized and active human being in society. This proposal, we think that the teaching and learning process will have a pedagogical growth, which will offer means and paths for these students, to be protagonists of their learning throughout their lives.
Keywords: Ambientes itinerantes de aprendizagem; Educação física; Educação inclusiva; Pedagogia Inaciana; Itinerant learning environments; Physical education; Inclusive education; Ignatian pedagogy